Between support and scepticism: Health professionals’ perceptions of a nutrition education program promoting low-carbohydrate, high-fat diets in under-resourced South African communities - Georgina Pujol-Busquets; Kate Larmuth; Christopher C. Webster; James Smith; Ahtisham Younas; Sergi Fàbregues; Anna Bach-Faig (PLoS ONE, 2025)
The burden of non-communicable diseases (NCDs) continues to rise, emphasizing the need for effective dietary interventions. Programs such as Eat Better South Africa (EBSA) advocate for low-carbohydrate high-fat (LCHF) dietary choices, especially in disadvantaged communities. However, the adoption of such approaches among healthcare professionals remains contentious. This qualitative study explores healthcare professionals’ perspectives on nutrition and the EBSA program, drawing on 16 in-depth individual interviews with physicians, nurses, and dietitians from False Bay Hospital, Groote Schuur Hospital, and a primary health clinic in Hout Bay, Western Cape, South Africa. Thematic analysis of the interviews revealed four main findings. Healthcare professionals lacked confidence in their nutritional knowledge, and while many were familiar with the LCHF diet, opinions varied regarding its sustainability and health implications. Concerns were raised about the high fat content and affordability of LCHF foods. Professionals acknowledged the value of group support in behaviour change, as promoted by EBSA, but expressed reservations about its strong emphasis on LCHF diets. Key challenges identified for patients included poverty, cultural beliefs, limited education, and access to nutritious foods. The findings highlight a reliance on traditional dietary advice, with uncertainties about the feasibility and affordability of LCHF diets. These findings offer novel insights into the complexities of implementing community-based dietary interventions in South Africa, with implications for policy and practice.